2021
DOI: 10.1111/jcmm.16337
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 promotes tumorigenicity of cervical cancer by up‐regulating CDK6

Abstract: Erythropoietin‐producing hepatocellular receptor A2 (EphA2) receptor tyrosine kinase plays an important role in tissue organization and homeostasis in normal organs. EphA2 is overexpressed in a variety of types of solid tumours with oncogenic functions. However, the role of EphA2 in cervical cancer (CC) is still needed to be further explored. Here, we examined the role of EphA2 by establishing a stable EphA2 knock‐down CC cell lines or a stable EphA2‐overexpressed CC cells lines. Overexpression of EphA2 increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…EPHA2 protein expression exhibited upregulation in CC cell lines, leading to increased cell proliferation and migration of CC. EPHA2 knockdown increased the cellular susceptibility to epirubicin in CC cells and suppressed CC growth in a xenograft mouse model [ 69 ].…”
Section: Cervical Cancermentioning
confidence: 99%
“…EPHA2 protein expression exhibited upregulation in CC cell lines, leading to increased cell proliferation and migration of CC. EPHA2 knockdown increased the cellular susceptibility to epirubicin in CC cells and suppressed CC growth in a xenograft mouse model [ 69 ].…”
Section: Cervical Cancermentioning
confidence: 99%
“…A high level of CD21 was found in HPV+/EBV+ NPCs, when compared to EBV-/HPV- tumors ( p = 0.0194), although no difference was observed between HPV+/EBV+ NPCs and those harboring EBV or HPV single infections [ 7 ]. Furthermore, increased levels of EphA2, the epithelial EBV receptor, was evidenced in CIN and cervical carcinomas when compared to normal cervical epithelium, and also correlated with CDK6 protein expression [ 123 ]. In addition, a 15.28-fold increase in EphA2 receptor expression was observed in non-tumor cervical cells transfected with the HPV18 E2 gene [ 124 ].…”
Section: Possible Mechanisms Of Hr-hpv/ebv Cooperationmentioning
confidence: 99%
“…In present, studies have confirmed that high‐risk human papillomavirus (HPV) infection is the main cause of CC, about 95% of CC is related to HPV infection, leading to precancerous lesions and invasion of CC 67 . Recently, NF‐YA and EphA2 were identified as key regulators in the pathogenesis of CC, without detailed exploration in the clinical setting 68,69 . Therefore, it is of great clinical significance to deeply explore the pathogenesis of CC and find more potential molecular markers of CC.…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“… 67 Recently, NF‐YA and EphA2 were identified as key regulators in the pathogenesis of CC, without detailed exploration in the clinical setting. 68 , 69 Therefore, it is of great clinical significance to deeply explore the pathogenesis of CC and find more potential molecular markers of CC.…”
Section: Functions Of Circrnasmentioning
confidence: 99%